Nepal- A Four Decades Success Story in moving beyond the Micronutrient Targets of the World Fit for Children Goals. - Gautam, Mukunda. (Tufts University. Tisch Library., 2019)
This poster tells Nepal's success story in MDG Era.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy